Learning difficulties in area calculation: a case study of a Diploma in Quantity Surveying Student - Mohd Ghazali, Mohd Khairi Azhar; Nik Abdul Rahman , Nik Suryani; Abdul Rahman, Zainurin (2012)
Mathematics is a branch of knowledge that becomes the building blocks for other areas of knowledge. For example, a simple calculation of the area of a square could become into something more serious such as calculating the number of bricks needed to build a wall, which is part of quantity surveying. Although students have been exposed to the calculation of area from as early as upper primary education, some students still found that basic calculation of area as a daunting task. This problem becomes worse once the students enter into the higher level of study. Thus, by adopting a qualitative approach, this paper explored the difficulties in learning faced by a quantity surveying diploma student of a private college in area calculation using semi-structured interview questions. Three themes which were identified as the cause of the difficulties emerged, namely self – meaning of area from previous knowledge, memorization of solutions and absence of support. It is therefore suggested that mathematics educators understand mathematical solutions from the student’s point of view so as to plan for the possible corrective measures. Consequently, students would realize their mistakes, why their solutions are incorrect and hence learn from them.